The Impact of Renewable Energy Development on Economic Growth - Virgilijus Dirma; Laima Okunevičiūtė Neverauskienė; Manuela Tvaronavičienė; Irena Danilevičienė; Rima Tamošiūnienė (Energies)
The development of renewable energy resources significantly impacts economic growth, various aspects of which can be assessed. First, the sector contributes to job creation, as new technologies and projects require specialists in various fields, from engineering to installation. Second, investments in renewable energy drive economic growth as the private and public sectors increasingly invest in innovation and infrastructure. In addition, developing renewable energy sources can lower energy prices for consumers, increase market competition, and reduce dependence on imported resources. However, there are also challenges related to initial investment costs, technological barriers and required political support. To ensure the successful development of renewable energy sources, it is necessary to create a favorable legal and regulatory environment, as well as to promote education and training in this area. In conclusion, the development of renewable energy resources can become an important driver of economic growth but requires a balanced approach and strategic planning. This work aims to evaluate the impact of the use of renewable resources on the economy after examining theories of economic growth. The following methods are used: analysis of theoretical and practical statements, comparative analysis, and panel data analysis. The research rejects hypotheses which suggest that transitioning to renewable energy sources slows economic growth. The development and adoption of renewable energy resources are essential for reducing greenhouse gas emissions, improving air quality, and ensuring sustainable development in the European Union. Despite initial costs and the hypothesis that transitioning to renewable energy slows economic growth, research shows that renewable energy sources (RES) do not hinder growth in the long term. Instead, they drive economic growth through technological advancements, job creation, and attracting significant investments, ultimately contributing to environmental protection and energy stability.